Upaya Peningkatan Kebutuhan Nutrisi Pada Pasien Hiperemesis Gravidarum Di Rsu Assalam Gemolong - Alvenia, Lia; , Sulastri, S.Kp., M.Kes (2016)
Hyperemesis Gravidarum is severe nausea and vomiting in pregnancy unruly. This conditions to complications in the fetus that low birth weight, premature birth and abortion. Hyperemesis gravidarum of complications is not just happening in the fetus but also mother to cause weight loss, dehydration, lack of nutrition. Important hyperemesis gravidarum is done bay changing, improved nutrition, eating, small portions, a little but often in warm and varied, dietary and fluid administration, and the provision of vitamis, in order to minimize the occurrence of excessive nausea and vomiting and there are no complications. Objective: of this research is to improve nutrition in patients with heg. Methods: This research uses descriptive method by collecting data in fact, conduct the implementation and evaluation. Results: in this study may be how changes in diet and proper diet can boost weight back, look no dehydration, and nausea in pregnant women generally limits normal.